Fuentes de financiamiento y desarrollo de las microempresas de la ciudad de Requena, 2023 - Bernuy Flores, Ana Cristina (2024)
The objective of this research is to determine the relationship between financing sources and the development of microenterprises in the city of Requena, 2023. To carry out this study, applied research, descriptive and correlational level, non-experimental design was used. The population was made up of 235 microentrepreneurs, from which a sample of 146 people was extracted, who were surveyed using a questionnaire. Obtaining as results that the level of access to financing sources is regular (27%) and is followed by 23% which indicates a low level of access, although the initial capital and the capitalization of profits are sometimes sufficient for the operation, the Lack of knowledge about interest rates on loans and the use of credit cards as a source of financing are distinctive elements. Regarding the level of development of microenterprises, they are in a regular stage (29%) and 21% have a very low development, since creativity and innovation in the work environment is not encouraged regularly, and the encouragement for the team to propose innovative ideas is almost non-existent. Finally, it was determined that there is a positive and significant relationship between the variables, corroborated by a coefficient of 0.784 and a significance with a value of 0.000.